Unusual Etiology of Acute Wrist Pain: Acute Calcific Tendonitis of the Flexor Carpi Ulnaris Mimicking an Infection - Man R. Shim (Case Reports in Orthopedics)
Acute calcific tendonitis is a common cause of musculoskeletal pain. However, it seldom affects the hand and wrist. For that reason, it is frequently mistaken for more common etiologies. This study reports a case of acute calcific tendinitis of the flexor carpi ulnaris, which was initially misdiagnosed as cellulitis, in a 65-year-old woman, who was unnecessarily prescribed with antibiotics. However, further evaluation confirmed the correct diagnosis of acute calcific tendinitis and her symptoms were subsequently resolved within 2 weeks with rest, wrist immobilization, and an intake of anti-inflammatories. This case underscores the need for the physicians to be aware of this less common but important cause of acute wrist pain in order to prevent misdiagnosis and avoid unnecessary medical treatments.